Effectiveness Of Deep Breathing Relaxation Therapy On Reducing Pain In Post-Operative Patients In The Recovery Room - Rezqiqah Aulia Rahmat; Nur Asmah (International Journal of Health Sciences, 2026)
ABSTRACT Postoperative pain is a common problem experienced by patients after surgery and can impact their recovery. One non-pharmacological method that can be used to reduce pain is deep breathing relaxation therapy. This study aimed to determine the effectiveness of deep breathing relaxation therapy on reducing post- operative pain in patients in the recovery room. This research uses a quantitative approach with a pre-experimental design through the one-way method. group pretest-posttest The research sample consisted of 30 postoperative patients selected using purposive sampling techniques. Pain levels were measured before and after deep breathing relaxation therapy using a numeric scale . Rating Scale (NRS). Data were analyzed using the Paired T- test . The results of the study showed a decrease in the average pain level after deep breathing relaxation therapy. The average pain score before the intervention was 6.73 and after the intervention decreased to 3.87. The statistical test results showed a p value of 0.000 (p < 0.05), indicating a significant effect of deep breathing relaxation therapy on reducing pain in postoperative patients . post- operative pain levels in patients in the recovery room. This therapy can be used as a non-pharmacological nursing intervention to help improve patient comfort. Keywords: Deep Breathing Relaxation, Postoperative Pain, Nonpharmacological Therapy , Recovery Room